AAAPT Diagnostic Criteria for Acute Low Back Pain with and Without Lower Extremity Pain. Issue 11 (11th September 2020) - Nicol, Andrea L; Adams, Meredith C B; Gordon, Debra B; Mirza, Sohail; Dickerson, David; Mackey, Sean; Edwards, David; Hurley, Robert W
Abstract: Objective: Low back pain is one of the most common reasons for which people visit their doctor. Between 12% and 15% of the US population seek care for spine pain each year, with associated costs exceeding $200 billion. Up to 80% of adults will experience acute low back pain at some point in their lives. This staggering prevalence supports the need for increased research to support tailored clinical care of low back pain. This work proposes a multidimensional conceptual taxonomy. Methods: A multidisciplinary task force of the ACTTION-APS-AAPM Pain Taxonomy (AAAPT) with clinical and research expertise performed a focused review and analysis, applying the AAAPT five-dimensional framework to acute low back pain. Results: Application of the AAAPT framework yielded the following: 1) Core Criteria: location, timing, and severity of acute low back pain were defined; 2) Common Features: character and expected trajectories were established in relevant subgroups, and common pain assessment tools were identified; 3) Modulating Factors: biological, psychological, and social factors that modulate interindividual variability were delineated; 4) Impact/Functional Consequences: domains of impact were outlined and defined; 5) Neurobiological Mechanisms: putative mechanisms were specified including nerve injury, inflammation, peripheral and central sensitization, and affective and social processing of acute low back pain. Conclusions: The goal of applying the AAAPT taxonomy to acute low back pain is to improve its assessment through a defined evidence and consensus-driven structure. The criteria proposed will enable more rigorous meta-analyses and promote more generalizable studies of interindividual variation in acute low back pain and its potential underlying mechanisms.